Climate signals in stable carbon and hydrogen isotopes of lignin methoxy groups from southern German beech trees [data] - Wieland, Anna; Greule, Markus; Roemer, Philipp; Esper, Jan; Keppler, Frank (Universität, 2022)
Stable hydrogen and carbon isotope ratios of wood lignin methoxy groups (δ13CLM and δ2HLM values) have been shown to be reliable proxies of past te...
Gesehen am 27.10.2022
Keywords: Forschungsdaten; Datenbank